Tinjauan Yuridis Terhadap Tindak Pidana Siber - Irawan, Dhanny (Pusat Penelitian dan Pengembangan Polri, 2025)
As the front line in combating cybercrime, the Indonesian National Police (Polri) often encounters challenges related to prevailing laws and regulations. For instance, cyber investigators at the regional police level (Polda/Polres) are required to obtain permission from central banking institutions located in Jakarta to trace the bank accounts of individuals suspected of committing cybercrimes. This situation leads to a legal gap, where what is mandated by law or regulation does not always align with conditions in the field. It highlights that the enforcement of cybercrime laws by Polri faces various challenges in institutional, technical, and regulatory aspects. This study aims to map the dynamics of cybercrime handling at the Polda and Polres levels and to identify legal gaps and operational obstacles that hinder effective investigations. Using a mixed-method approach, data were collected through questionnaires, focus group discussions, and document studies conducted across 11 regional police departments (Polda). The findings reveal disparities in investigative capabilities across regions, limited availability of digital forensic tools, and regulatory barriers related to accessing information from banking institutions and digital platforms. There is an urgent need for internal reform within Polri, including capacity-building for human resources, provision of adequate infrastructure, and strengthening cross-sectoral cooperation. On the regulatory side, revisions to the Electronic Information and Transactions Law and Banking Law are recommended, along with the formulation of specific regulations requiring digital service providers to support investigative processes. This research emphasizes the importance of progressive and adaptive approaches in addressing the increasingly complex nature of cybercrime.